Pemberdayaan Pemuda Pertanian Melalui Edukasi Pertanian Organik di Desa Trucuk Kecamatan Trucuk Kabupaten Bojonegoro - Badi’atud Durroh; Yudha, Danang Ananda; Anang Kurniawan; Dilla Yesita Sari; Masahid Masahid (Asosiasi Riset Ilmu Tanaman Dan Hewan Indonesia, 2024)
The role of the younger generation in improving quality in the agricultural sector has a very crucial role. However, nowadays soil fertility in Indonesia is decreasing day by day as agricultural land use becomes more intensive. So that young people's insight regarding environmentally friendly cultivation techniques through organic farming needs to be added and strengthened to create progress in the fields of agriculture and food security. The aim of this service activity is an effort to increase the younger generation's understanding of organic farming through counseling and creating demonstration plots for organic vegetable cultivation using vegetable pesticides and liquid organic fertilizer (POC) to increase agricultural products and stabilize the economy of the surrounding community. The activity method is carried out through counseling, socialization and direct practice through making demonstration plots. Counseling about organic farming and its impact on the environment. The demonstration plot focused on the correct working methods and techniques in organic farming through the application of liquid organic fertilizer (POC) and vegetable pesticides. Following this community service activity program, it shows that the knowledge and skills of the younger generation of farmers have increased regarding organic vegetable cultivation and the impact of organic farming on the environment. Keyword: organic fertilizer, agriculture, demonstration plots, environment